2019
DOI: 10.1210/en.2019-00261
|View full text |Cite
|
Sign up to set email alerts
|

Castration Determines the Efficacy of ETAR Blockade in a Mouse Model of Prostate Cancer Bone Metastasis

Abstract: Bone metastasis is a painful complication of advanced prostate cancer. Endothelin-1 is a tumor-secreted factor that plays a central role in osteoblast activation and the osteosclerotic response of prostate cancer metastatic to bone. Antagonists that block the activation of the endothelin A receptor (ETAR), located on osteoblasts, reduce osteoblastic bone lesions in animal models of bone metastasis. However, ETAR antagonists demonstrated limited efficacy in clinical trials of men with advanced prostate cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Among these, IGF1 activates phosphoinositide 3-kinase (PI3K)/Akt mammalian target of rapamycin (mTOR) pathway, with subsequent breast cancer cell growth, proliferation, and migration into the bone [17,61,62]. Osteoblasts can also be regulated by metastatic tumor cell-derived factors including endothelin 1 (ET1), dickkopf 1 (DKK1), and the Wnt signaling cascade [36,[63][64][65][66]. While Wnt promotes osteoblast differentiation, its activity can be inhibited by DKK1, which is an antagonist in this cascade.…”
Section: Biological Mechanisms Of Bone Metastasismentioning
confidence: 99%
“…Among these, IGF1 activates phosphoinositide 3-kinase (PI3K)/Akt mammalian target of rapamycin (mTOR) pathway, with subsequent breast cancer cell growth, proliferation, and migration into the bone [17,61,62]. Osteoblasts can also be regulated by metastatic tumor cell-derived factors including endothelin 1 (ET1), dickkopf 1 (DKK1), and the Wnt signaling cascade [36,[63][64][65][66]. While Wnt promotes osteoblast differentiation, its activity can be inhibited by DKK1, which is an antagonist in this cascade.…”
Section: Biological Mechanisms Of Bone Metastasismentioning
confidence: 99%
“…However, a placebo-controlled phase III trial showed the ineffectiveness of atrasentan in delaying the progression of bone metastatic lesions in castrate-resistant prostate cancer [ 230 ]. Interestingly, a preclinical study on zibotentan demonstrated that the effectiveness of that endothelin A inhibitor considerably depends on androgen ablation [ 231 ].…”
Section: Emerging Targeted Therapiesmentioning
confidence: 99%
“…These data, together with results from other solid tumors, make the use of ET axis inhibitors a promising approach toward PCa progression and metastasis. Although, in a recent meta-analysis, the use of ET-A receptor antagonists with or without docetaxel was not proven to offer improvement in survival or disease progression for CRPC, other recent data suggest that ET-A blockade is most efficacious when combined with complete androgen deprivation for the control of bone metastases [ 186 , 187 ].…”
Section: Molecular Events Governing Emt In Cancer Progressionmentioning
confidence: 99%